OCCUPATIONAL PSYCHOLOGY IN HIGHER EDUCATIONAL INSTITUTIONS: A STUDY IN PAKISTAN - Mangi, Riaz Ahmed; Jalbani, Amanat Ali (European Scientific Journal, ESJ, 2013)
The work engagement and job burnout are rapidly emerging areas in research on human resources management and occupational psychology in Pakistan. This study is conducted to investigate and estimate the work engagement its relationship with organization commitment and burnout among the faculty of higher education institutions. The population for this study comprised faculty members of higher education institutions employing approximately 100 or more than 100 faculty members. All the male and female faculty members working in different departments are included in the sample of the study. In this study, convenient sampling method applied to collect the data. UWES (Utrecht Work Engagement Scale), MBI-GS (Maslach Burnout Inventory-General Survey) and organizational commitment scale. The relationship between the dimensions and the study constructs are significant. All the dimensions of burnout are significantly and negatively predicting work engagement among the respondents. Two dimensions of work engagement are positively and significantly predicting organizational commitment among the respondents. Two dimension of burnout are negatively predicting organizational commitment among the respondents.